Recent advances in asthma genetics - Moffatt, Miriam (Henry Stewart Talks, 2011)
Incidence of asthma, Environment and genetic causes, Disease identification prior to completion of sequencing of the human genome, Genome Wide Association Study (GWAS), Omic technologies including global gene expression, GABRIEL and Asthma susceptibility genes identified by GWAS, Asthma and infection, 16S rRNA and metagenomics, What next